A Case Study of the Socio-Economic Conditions of Workers in Factory A and Factory B / Agatha Foo Tet Sin - Agatha, Foo Tet Sin (1984)
This case study is a comparison of the socio-economic problems of workers in Factory A and Factory B. In order to provide a clear and systematic picture, the researcher has arranged this study into various chapters. Chapter One gives a general introduction of the objectives and significance of the study. It also discusses the research methodology used and the problems encountered during the research. In Chapter Two, a general overview of the factories is presented, with the discussion ranging from 'who are the employers' to 'why does the Government accommodate them'. Chapter Three deals with the terms of employment. It shows the similarities and differences between the employment policies and working conditions faced by workers in Factory A and Factory B. A deeper description of the structure of labour force is depicted in Chapter Four. It shows a distinction between workers of Factory A and Factory B, with regards to their race, sex, age level, working experience, etc. Chapter Five attempts to explain some of the causes of the workers' present socio-economic status, with emphasis on their poor level of education achievement. The discussion in Chapter Six is focussed mainly on the industrial relations in the factories. The concluding Chapter, is devoted to elaborating some of the limitations of the study and some suggestions of how to improve it. There is also a short summary of the findings accompanied by some recommendations.